Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Synthesis of hierarchically micro-mesoporous carbon nanospheres: Molecular insight into the role of hexamethylenetetramine on the pore architecture - Ran Yuan; Shuxia Yuan; Yu Yang; Chunxiang Lu; Guohua Sun; Shijie Wu; Xiaodan Ren; Hao Cui (Chemical Engineering Journal, 2026)

Volatile methylsiloxanes in a textile dyeing and printing industrial park: Source profiles, ambient distributions and SOA formation potential - Xiaodie Pang; Hao Han; Wei Song; Xiangyu Zhang; Ran An; Jianqiang Zeng; Chao Peng; Weiqiang Yang; Chenshuo Ye; Xiao Tian; Hongcheng Lu; Zhou Zhang; et al. (Journal of Hazardous Materials, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Ligand-specific tuning of an olfactory receptor to respond to sex pheromones in cowpea weevil, Callosobruchus maculatus - Hao-Ran Lu; Shan Li; Li-Jie Zhang; Kai Shi; Si-Qin Ge; Zhen Zou (Insect Biochemistry and Molecular Biology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A comprehensive review of emerging protein modification methods: modified properties and potential applications - Hao Zhu; Kaifang Guan; Xiaolin Liu; Ran Xiao; Ying Ma; Weihong Lu; Xue Han; Rongchu Wang; Tianjiao Niu (Food Chemistry, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Simulation study on burning flux of biodiesel/NH3/CO2/H2O flames with consideration of radiation reabsorption - Hao Liu; Shu Zheng; Tipeng Wang; Ran Sui; Qiang Lu (Fuel, 2026)

MHC II system of mandarin fish (Siniperca chuatsi): Gene identification, expression analysis and transcriptional regulation - Jing Hou; Lu Qi; Ran Cao; Lan Hao Liu; Shan Nan Chen; Pin Nie (Aquaculture, 2026)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Corrigendum to “Chronic oral depleted uranium leads to reproductive damage in male rats through the ROS-hnRNP A2/B1-COX-2 signaling pathway” [Toxicology 449 (2021) 152666] - Binghui Lu; Yonghong Ran; Shuang Wang; Juan Li; Yazhen Zhao; Xinze Ran; Rong Li; Yuhui Hao (Toxicology, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

Deciphering the physiological response mechanisms of Miscanthus sinensis to salt-induced stress - Hai-Long Lu; Ling Li; Jackson Nkoh Nkoh; Jian-Jian Li; Hao-Ran Wang; Xiao-Hui Li; Dong-Li Hao; Jun-Qin Zong (Biomass and Bioenergy, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Central core regulation by methoxy in quinoxaline-based non-fullerene acceptors for over 19 % efficiency organic solar cells - Huijuan Bi; Dingding Qiu; Hao Zhang; Caixuan Wang; Mengying Wu; Xinya Ran; Jianqi Zhang; Yuheng Wang; Ailing Tang; Xinyang Miao; Zhixiang Wei; Kun Lu (Chemical Engineering Journal, 2025)

CRISPR/Cas13a-mediated visual detection: A rapid and robust method for early detection of Nosema bombycis in silkworms - Yi-Xiang Wu; Samreen Sadiq; Xin-Hao Jiao; Xue-Min Zhou; Lu-Lai Wang; Xin-Ran Xie; Iltaf Khan; Ping Wu (Insect Biochemistry and Molecular Biology, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Efficient adsorption of pesticides by porous organic polymers based on imine/aminal linkages - Aiguo Yang; Tong Wang; Jiawen Wu; Chenggang Hao; Weijiang Gan; Zhaojin Ran; Xuecai Tan; Zhongmin Wang; Kecheng Lu (Journal of Water Process Engineering, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Estrogen-related receptor, a molecular target against lepidoptera pests - Guan Wang Shen; Die Liu; Hao Ran Xu; Lu Yu Hou; Jin Xin Wu; Qing You Xia; Ping Lin (Pesticide Biochemistry and Physiology, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Effects of simultaneous CO2 addition to the fuel and oxidizer streams on soot formation in co-flow diffusion ethylene flame - Yu Yang; Shu Zheng; Yuzhen He; Hao Liu; Ran Sui; Qiang Lu (Fuel, 2023)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Impact of π–bridge unit in fully nonfused ring electron acceptor on the photovoltaic performance of organic solar cells - Wenlong Liu; Xinming Zheng; Guangliu Ran; Hao Lu; Xinjun Xu; Chuang Yao; Yahui Liu; Wenkai Zhang; Zhishan Bo (Chemical Engineering Journal, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Elucidation of the electrocatalytic activity origin of Fe3C species and application in the NOx full conversion to valuable ammonia - Ran Hao; Shasha Fang; Lu Tian; Runlin Xia; Qingxin Guan; Lifang Jiao; Yuping Liu; Wei Li (Chemical Engineering Journal, 2023)

Endophytic fungus Trichoderma atroviride D16 increases tanshinone accumulation in Salvia miltiorrhiza plantlets by enhancing abscisic acid and salicylic acid signaling - Xing-Guang Xie; Ke-Xin Sheng; Wei-Lan Lu; Hao-Ran Wang; Khalid Rahman; Kun-Miao Feng; Ting Han (Symbiosis, 2023)

Airborne PM2.5 pollution: A double-edged sword modulating hepatic lipid metabolism in middle-aged male mice - Renjie Hu; Lu Zhang; Li Qin; Hao Ding; Ran Li; Weijia Gu; Rucheng Chen; Yunhui Zhang; Sanjay Rajagoplan; Kezhong Zhang; Qinghua Sun; Cuiqing Liu (Environmental Pollution, 2023)

Depleted uranium causes renal mitochondrial dysfunction through the ETHE1/Nrf2 pathway - Suiyi Liu; Shuang Wang; Yazhen Zhao; Juan Li; Chang Shu; Yong Li; Jie Li; Binghui Lu; Zeheng Xu; Yonghong Ran; Yuhui Hao (Chemico-Biological Interactions, 2023)

Clinical evaluation of efficacy of leflunomide combined with low-dose prednisone for treatment of myasthenia gravis - Xin Huang; Li Qiu; Yaru Lu; Jiaxin Chen; Wenhao Yang; Changyi Ou; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2023)

A Review of Uranium-Induced Reproductive Toxicity - Shuang Wang; Yonghong Ran; Binghui Lu; Juan Li; Hongrong Kuang; Li Gong; Yuhui Hao (Biological Trace Element Research, 2020)

Structure–activity relationship investigation of coumarin–chalcone hybrids with diverse side-chains as acetylcholinesterase and butyrylcholinesterase inhibitors - Lu Kang; Xiao-Hui Gao; Hao-Ran Liu; Xue Men; Hong-Nian Wu; Pei-Wu Cui; Eric Oldfield; Jian-Ye Yan (Molecular Diversity, 2018)

Global mapping of artificial surfaces at 30-m resolution - XueHong Chen; Xin Cao; AnPing Liao; LiJun Chen; Shu Peng; Miao Lu; Jin Chen; WeiWei Zhang; HongWei Zhang; Gang Han; Hao Wu; Ran Li (Science China Earth Sciences, 2016)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

Endothelium-specific SIRT1 overexpression inhibits hyperglycemia-induced upregulation of vascular cell senescence - HouZao Chen; YanZhen Wan; Shuang Zhou; YunBiao Lu; ZhuQin Zhang; Ran Zhang; Feng Chen; DeLong Hao; Xiang Zhao; ZhiChen Guo; DePei Liu; ChihChuan Liang (Science China Life Sciences, 2012)